2013
DOI: 10.1177/0036933013482635
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR testing requires a robust multi-disciplinary strategy to effectively manage identified cases of chlamydial conjunctivitis

Abstract: New PCR technology has resulted in a shared care approach to address corresponding implications of testing. Effective communication with a structured protocol and a central point of contact has improved follow-up and ensures appropriate best practice management of chlamydial conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…At that time, the inability of viral culture for this pathogen led the investigators to assume that it was a virus. With improved diagnostic technology, physicians currently use PCR or ELISA to help detect the pathogen [7] , [8] . In our case, we also performed Giemsa statin and obtained the intracytoplasmic inclusion, which made us more confident of our diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, the inability of viral culture for this pathogen led the investigators to assume that it was a virus. With improved diagnostic technology, physicians currently use PCR or ELISA to help detect the pathogen [7] , [8] . In our case, we also performed Giemsa statin and obtained the intracytoplasmic inclusion, which made us more confident of our diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Scotland showed that 4% of eye swabs tested by a multiplex PCR panel were positive for chlamydia 8. This study highlighted the importance of having a robust follow-up system in place for parents to ensure that treatment is not delayed.…”
Section: Physiological Backgroundmentioning
confidence: 93%
“…Our aim was to compare the recorded clinical management with these locally chosen standards and to see if the lessons and solutions identified previously were still being followed [19].…”
Section: Methodsmentioning
confidence: 99%
“…This means positive OC results can be identified following routine conjunctival swabbing, and this situation led to a formal complaint regarding a positive test in a young teenager, raising medico-legal implications regarding STI testing in children [16][17][18]. We have previously published that 4% of the 1914 patients swabbed for presumed viral conjunctivitis in the West of Scotland region in the calendar year following the introduction of this testing method in 2007 were found to have OC [19]. This represented a potentially undiagnosed cohort of individuals with a STI and it follows that a robust system should be in place to address this predictable clinical situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation